Analisis Pushover terhadap Struktur Gedung dengan Sistem Rangka Pemikul Momen Khusus menggunakan Metode Precast - septiarsilia, Yanisfa; Propika, Jaka; Susanti, Eka; Prasetyo, Agus Edy (AGREGAT, 2024)
The ITS Tower 2 building was built on Keputih Street, Surabaya. This building has 13 floors with a height of +51.00 meters which was built using a conventional concrete system. Based on the structural analysis results, the authors found that the existing structure was included in the category of soft soil (SE). In SNI 2847-2019 for the Special Structural Wall Systems category, the building height had a maximum limit of 48 meters. Conventional system planning took a relatively long time to complete. So it was necessary to evaluate the existing structure and modify it using the SMRF method and Precast System. The SMRF-method was used because it did not have a height limit in its planning, and the precast system was chosen because the planned structure had a typical floor plan. The evaluation of the existing structure showed that the fundamental period was 1.2384 seconds, the mass participation in the X direction was 93.90%, the Y direction was 91.79% with 75 modals, and the most significant floor deviation occurred in the Y direction was 49.57 mm. This value met the requirements according to SNI 2847-2019 and SNI 1726-2019; several beam and column cross-section elements are still unsafe due to the reinforcement being smaller than the analysis result, but the performance level was included in the Immediate Occupancy. The evaluation results of the structure showed that the main beam B2 was 60/80 with the longitudinal reinforcement 8D29, the joist beam B4 was 50/70 and B6 was 40/60 with the longitudinal reinforcement 7D25, the column K1 was 110/110 with the longitudinal reinforcement 28D36. The structural behavior obtained the entire period of 1.6059 seconds, the mass participation in the X direction was 99.30%, the Y direction was 99.24% with 50 modals, and the most significant floor deviation occurred in the Y direction was 28.46 mm. This value met the requirements and performance of the building, including the Immediate Occupancy level. Connections for precast columns used dry joints, while the connections for other precast elements used wet joints.